Damage growth and failure detection in hybrid fiber composites using experimental in-situ optical strain measurements and smoothing element analysis. (April 2022) - Tabrizi, Isa Emami; Kefal, Adnan; Zanjani, Jamal Seyyed Monfared; Yildiz, Mehmet
In previous study the failure initiation and development in hybrid fiber laminates was successfully monitored and determined. In current investigation a novel damage monitoring approach is proposed for hybrid laminates by combining different optical strain measurement techniques namely digital image correlation (DIC), fiber Bragg grating sensors (FBG) and infrared thermography (IRT) with smoothing element analysis (SEA). This viable experimental procedure eliminates the effects of global/local nature of optical strain measurement systems on heterogeneous damage accumulation and is a two-step approach. First, all optical sensing systems together with conventional strain gauges are utilized concurrently to indicate the differences in the measured strains and monitor damage accumulation under tensile loading. This demonstrates how failure events disturb the measurement capabilities of optical systems, which can cause a miscalculation of hybrid effect in hybrid-fiber laminates. The second step involves the utilization of SEA algorithm for discretely measured DIC displacements to predict a realistic continuous displacement/strain map and rigorously mitigate the inherent noise of the full field optical system. Remarkably, for large deformation states in hybrid composites, the combination of SEA/DIC enables early prediction of susceptible damage zones at stress levels 30% below material strength.